Civil servants on the silver screen : Hollywood's depiction of government and bureaucrats - Pautz, Michelle C. (Politics, literature, & film., 2018)
This book demonstrates how government bureaucracy is portrayed in the top ten box office grossing films from 2000-2015. Perhaps unsurprisingly, government is generally portrayed poorly, but individual government bureaucrats are typically depicted positively.